Constraints on hand-foot coordination associated with phase dependent modulation of corticospinal excitability during motor imagery - Nakagawa, Kento; Kawashima, Saeko; Fukuda, Kazuki; Mizuguchi, Nobuaki; Muraoka, Tetsuro; Kanosue, Kazuyuki (Frontiers in Human Neuroscience, 2023)
Interlimb coordination involving cyclical movements of hand and foot in the sagittal plane is more difficult when the limbs move in opposite directions compared with the same direction (directional constraint). Here we first investigated whether the directional constraint on hand-foot coordination exists in motor imagery (imagined motion). Participants performed ten cyclic coordinated movements of right wrist flexionextension and right ankle dorsiflexion-plantarflexion as quickly and precisely as possible, in the following three conditions; 1) actual movements of the two limbs, 2) imaginary movements of the two limbs, and 3) actual movement of one limb combined with imaginary movement of the other limb. Each condition was performed under two directions; the same and the opposite direction. Task execution duration was measured as the time between the first and second press of a button by the participants. The opposite directional movement took a significantly longer time than did the same directional movement, irrespective of the condition type. This suggests that directional constraint of hand-foot coordination occurs even in motor imagery without actual motor commands or kinesthetic signals. We secondarily examined whether the corticospinal excitability of wrist muscles is modulated in synchronization with an imaginary foot movement to estimate the neural basis of directional constraint on imaginary hand-foot coordination.The corticospinal excitability of the forearm extensor in resting position increased during dorsiflexion and decreased during plantarflexion similarly in both actual and imaginary foot movements. This corticospinal modulation depending on imaginary movement phase likely produces the directional constraint on the imaginary hand-foot coordination.